Investigation of Corrosion Inhibition of Carbon Steel by Using Natural Iraqi Plum Tree Gum in a Saline Medium - Husseini, Marwah; Latief, Baraa H.; Khudhair, Noor Ali; Huseeni, Mustafa D; Al-Saadi, Farah Aziz (Iraqi Journal of Science, 2024)
In response to the growing interest in green chemistry and the adoption of environmentally friendly and cost-effective compounds in industrial and agricultural applications, this study focuses on exploring the potential of natural compounds. Specifically, the research investigates the corrosion inhibitory properties of Iraqi plum tree gum. The natural gum is characterized using Fourier transform infrared spectroscopy to identify its functional groups and atomic force microscopy (AFM) for further analysis. The electrochemical polarization technique was used to study corrosion measurements for carbon steel (C.S) in saline solution and in the presence of the inhibitor (Plum Tree Gum) in different concentration solutions. The findings revealed a positive correlation between the concentration of plum tree gum and the efficiency of the inhibitor, indicating that higher concentrations of the gum result in increased inhibitory effectiveness.